Assessment of ovarian reserve after hysterectomy: Laparoscopic vs. non-laparoscopic surgery. (March 2017) - Cho, Hye-yon; Park, Sung Taek; Kyung, Min Sun; Park, Sung-ho
Abstract: Objectives: To evaluate changes of ovarian reserve after hysterectomy by comparing serum anti-Mullerian hormone (AMH) levels following laparoscopic hysterectomy (LH) to those of non-laparoscopic hysterectomy (non-LH). Methods: Prospectively, serum AMH levels were measured pre-operatively (AMH0), 7 days (AMH1), 2 months (AMH2), and 6 months (AMH3) after LH (total laparoscopic hysterectomy or laparoscopy-assisted vaginal hysterectomy) and non-LH (vaginal hysterectomy or abdominal hysterectomy) in 91 premenopausal women (LH = 60, non-LH = 31). Changes of serum AMH levels were compared between the two groups. Results: AMH0 was similar between the two groups ( P = 0.400). Also, AMH1, AMH2, and AMH3 were not different between the two groups ( P = 0.333, 0.534, and 0.726). A significant decrease of serum AMH level (30% decreases from AMH0) at 7 days, 2 months, and 6 months was observed in 44.4%, 34.8%, and 40% of all patients. Interestingly, the incidence of a significant decrease of serum AMH levels at postoperative 2 months was considerably higher in LH group compare to non-LH group (43.9% vs. 20.0%, P = 0.042). Multivariate analysis revealed that laparoscopic hysterectomy was an independent risk factor for the significant decrease of serum AMH at postoperative 2 months (Hazard ratio 4.147, 95% confidence interval 1.139–15.097). Conclusion: Laparoscopic hysterectomy, which is associated with electro-thermal vessel ligation, might have negative effect on ovarian reserve after surgery. More large-scaled, long-term follow-up study is required.